Penegakan Hukum Adat Dayak oleh Damang dalam Penyelesaian Sengketa Tanah Adat Berdasarkan Perda Kalimantan Tengah Nomor 16 Tahun 2008 - Supian Sugiman; Heriamariaty; Rollys Suriani; Mulida Hayati; Novea Elysa Wardhani; Rico Septian Noor (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The existence of Dayak customary law in Central Kalimantan plays an important role in resolving customary land disputes. Recognition of customary institutions and the authority of the Damang (Customary Chief) is affirmed in Central Kalimantan Provincial Regulation Number 16 of 2008. In practice, customary land disputes in Kurun District are often resolved through customary legal mechanisms without proceeding to formal courts. This study aims to analyze the position and authority of the Damang in enforcing Dayak customary law and the process of resolving customary land disputes based on the regulation, with a case study of Damang Decree Number 02/DKA/KK/I/2026. This research employs a legal research method with an empirical juridical approach using statutory and case approaches. Data were collected through literature review and interviews with the Damang Customary Chief, Mantir Adat (customary officials), and the disputing parties, and were analyzed qualitatively. The results indicate that the Damang holds a recognized customary authority with normative legitimacy to enforce customary law and resolve customary land disputes. The dispute resolution process involves complaint submission, examination, customary deliberation, site inspection of the disputed land, and the issuance of a Damang Decree accepted by the disputing parties without further litigation in formal courts.